Política y ontología. Cara y cruz de Ortega - Blanco Fernández, Domingo (Revista de Filosofía, 2008)
In order to contribute to an evaluation of Ortega’s legacy, the following pages select two dimensions of his work: (I) the political proposals concerning Spain, valid in the essential, and (II) his metaphysical attempts to overcome the opposition idealism-materialism, that leaves side by side both incompatible thesis, on account of the absence of reflexion about sensorial selfintuition.
Keywords: Particularism; Executive I; Protagorism; Selfperception